Automatización e instrumentación del canal abierto del laboratorio de hidráulica del Departamento de Ingeniería Civil y Ambiental (2020)
In this work, the instrumentation and automation of the open irrigation channel present in the department of civil and environmental engineering of Universidad de Los Andes? hydraulics laboratory was developed. In the instrumentation part, the adaptation of pipes, assembly and connections of the remaining equipment in the channel, design of electrical plans and characterization of the level sensors were carried out. In the automation part, a filling sequence was designed, the transfer function that describes the behavior of the water level in the third section of the channel was characterized based on a setpoint of 30 cm, then an ON / OFF controller, a PID controller tuned by Wang-Juang-Chan method, and IMC-based PI and PID controllers were designed in order to keep the water level at the aforementioned setpoint. After conducting experimental tests with the controllers, it was observed that the IMC-based PI controller had a better performance than the others...